Adaptation of educational tasks for children with autism spectrum disorders - Khaustov A.V; Zagumennaya O.V (Moscow State University of Psychology and Education, 2016)
The article describes different methods of adaptation of educational materials for children with ASD who are receiving education in elementary school adapted basic educational programs. It contains examples of varied levels of adapted educational tasks for children with ASD who are studying four subjects in the first grade: mathematics, the Russian language, literary reading, environmental science. The article underlines key principles for the usage of adapted educational tasks. The materials were developed and tested on the base of the Center for Psychological, Medical and Social Support for Children and Adolescents of the Moscow State University of Psychology and Education. The presented adapted materials allow to realise adapted educational programs in accordance with the Federal State Educational Standards of Elementary General Education for students with disabilities. Adaptation of an educational task for a child with ASD is illustrated here with a concrete example.